Distribution Prediction of Shale Deformation Structures in Tectonically Complex Area Based on Relationship Between Geological Structures and Shale Deformation - Cheng, Guoxi; Jiang, Bo; Li, Fengli; Li, Ming; Song, Yu (Frontiers in Earth Science, 2022)
The alteration of shale structures and properties induced by tectonic activities is an important factor restricting the efficient utilization of shale gas resources. Predicting the distributions of shale deformation structures is of significance for the potential evaluation and favorable area optimization of shale resources in tectonically complex areas. Taking the Wufeng–Longmaxi shale of the southern Sichuan Basin as the research object, deformation observations of shale outcrops and shale core samples were conducted to reveal the distribution patterns of shale deformation structures in fault and fold structures. On this basis, the distribution rules of shale deformation structures in the unexposed areas were predicted by considering the structural framework of the study area. Our research indicated that faults can cause structural deformation in a limited area and that the influences of reverse faults were relatively more significant. Shale near the fault planes of reverse faults usually showed intense folding deformations, with well-developed bedding-parallel and crumpled cleavages. Strong deformation structures (crumpled, mylonitized, scaly, fractured-crumpled, and flaky structure) were distributed. Structural deformations in shale near normal faults were mainly characterized by the increase of tectonic fractures, and shale usually showed cataclastic structure. In the areas affected by strike-slip faults, bedding-perpendicular fractures and the fractures high-angle oblique to bedding planes were well developed. Folds can cause shale to deform in a larger area than faults. Shale in core zones usually displayed strong deformation structures. In the core–limb transitional areas of folds, shale mainly developed bedding-parallel and bedding-perpendicular fractures, and shale usually displayed platy and cataclastic structure. The observed structural deformations in fold limbs were generally weak, and shale usually showed primary structure and weak brittle deformation structures. According to the structural framework of the study area, it is predicted that strong deformation structures are mainly distributed in the core zones of anticlines (especially the tight and closed ones) and near the fault planes of large-scale reverse faults, while medium-intensity brittle deformation structures (platy and cataclastic structure) are distributed in core–limb transitional areas of anticlines and near the normal and strike-slip faults. In the limbs of anticlines and the areas controlled by synclines (mostly wide and gentle), shale mainly shows primary structure and weak brittle deformation structures.